Catabolic activity and biofilm formation of foodborne Listeria monocytogenes strains - Sharar, Nowshin Shyara; Chai, Lay Ching; Thong, Kwai Lin (Springer International Publishing, 2018)
Listeria monocytogenes is a major foodborne pathogen causing increased morbidity worldwide. It forms resistant biofilm structures in food processing facilities after sanitization, consequently creating a public health concern. Many studies on the metabolism and transmission of L. monocytogenes has provided insights into its intracellular infection process, however there is limited understanding on the substrate utilization of the bacteria. Therefore, the main objective of this study was to investigate the carbon and nitrogen substrate catabolism and the biofilm forming potential of 3 Malaysian L. monocytogenes strains (LM41, LM92 and LM115) previously isolated from ready-to-eat foods. Biolog Phenotype Microarray (PM) system was used to study the catabolic activity of the foodborne strains in 190 carbon and 380 nitrogen sources. PM analysis showed that the carbon and nitrogen catabolic activity of L. monocytogenes strains were considerably limited and these strains utilised Tween 40 and Tween 80, which are commonly used for the sanitation in food and meat processing industries. Furthermore, all 3 strains showed strong biofilm forming potential in nutrient-rich and nutrient-limited media, irrespective of the serogroups. The data generated could be utilised to develop alternative measure to inhibit biofilm formation in L. monocytogenes in the food processing environment.